PENGEMBANGAN E-MODUL MENGGUNAKAN PDF CORPORATE PADA MATERI SISTEM KOMPUTER DI SMPN 6 GARUT - Dwi Kurniatina, Riska; Rivan Syahrul Falah; Sofiah, Efi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop an e-module using Flip PDF Corporate for Computer Systems material, determine its feasibility based on material and media expert assessments, and describe students' responses after using the product. The study employed a Research and Development approach with the Alessi and Trollip model, which consists of planning, design, and development stages. The research subjects were one material expert, one media expert, and 28 students of class VIII-I at SMPN 6 Garut. Data were collected through observation, unstructured interviews, questionnaires, and documentation. The instruments used a five-point Likert scale, and the data were analyzed using mean scores. The planning stage identified limited learning resources and the dominance of textbooks and presentation media. The design stage produced a flowchart, storyboard, and interface design developed with Canva. The development stage generated an interactive flipbook containing structured material, images, videos, quizzes, a glossary, and supporting learning features. The material expert assessment obtained a mean score of 3.92 in the feasible category, the media expert assessment obtained 4.55 in the highly feasible category, and the student response obtained 4.26 in the very good category. These results indicate that the developed e-module is feasible as an alternative digital learning medium for Computer Systems material and is positively received by students.